Viral Coinfection Replaces Effects of Suilysin on Streptococcus suis Adherence to and Invasion of Respiratory Epithelial Cells Grown under Air-Liquid Interface Conditions - Meng, Fandan (Infect Immun, 2019)
Streptococcus suis is an important zoonotic pathogen which can infect humans and pigs worldwide, posing a potential risk to global public health. Suilysin, a pore-forming cholesterol-dependent cytolysin, is considered to play an important role in the pathogenesis of S. suis infections. It is known that infection with influenza A viruses may favor susceptibility to secondary bacterial infection, resulting in more severe disease and increased mortality. However, the molecular mechanisms underlying these coinfections are incompletely understood. Applying highly differentiated primary porcine respiratory epithelial cells grown under air-liquid interface (ALI) conditions, we analyzed the contribution of swine influenza viruses (SIV) to the virulence of S. suis, with a special focus on its cytolytic toxin, suilysin. We found that during secondary bacterial infection, suilysin of S. suis contributed to the damage of well-differentiated respiratory epithelial cells in the early stage of infection, whereas the cytotoxic effects induced by SIV became prominent at later stages of infection. Prior infection by SIV enhanced the adherence to and colonization of porcine airway epithelial cells by a wild-type (wt) S. suis strain and a suilysin-negative S. suis mutant in a sialic acid-dependent manner. A striking difference was observed with respect to bacterial invasion. After bacterial monoinfection, only the wt S. suis strain showed an invasive phenotype, whereas the mutant remained adherent. When the epithelial cells were preinfected with SIV, the suilysin-negative mutant also showed an invasion capacity. Therefore, we propose that coinfection with SIV may compensate for the lack of suilysin in the adherence and invasion process of suilysin-negative S. suis.